Adolescents' attitudes toward talking about books: implications for educators - Merga, Margaret; McRae, M.; Rutherford, L. (2018)
Young people’s frequency of engagement in reading books for pleasure markedly decreases as they move through the schooling years, reducing their exposure to this beneficial literacy practice. Young people’s perceptions of the value of reading can be socially mediated, and positive perception of the value of reading is associated with frequency of engagement in reading. As such, considering how to generate positive social interactions around reading is an important concern when seeking to increase young people’s reading frequency. We sought to investigate adolescents’ attitudes toward talking about books in order to identify reasons for engagement in discussion about books, as well as factors that constrained engagement in such discussions, with a view to informing best practice for educators seeking to engage adolescents in reading. The findings suggest that adolescents’ enjoyment of discussion about books may be related to common interests, enjoyment of discussion to facilitate critical exploration and comprehension, and the possibilities provided for recommendations and access. Adolescents’ interests in and ability to engage in book discussions was shaped by mutual text exposure, opportunity, personal preference, disinterested peers and social status maintenance. Findings are considered in relation to classroom practice, with formation of Special Interest Reading Groups within the classroom considered.